The Relationship between Family Support and Self-Esteem in Breast Cancer Patients Undergoing Palliative Care (A Correlational Study at Ulin Regional Hospital, Banjarmasin) - Khairunnisa; Nasution, Tina Handayani; Rahmayanti, Devi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
When an individual is diagnosed with breast cancer and must undergo treatment, the impact extends beyond physical health to psychological well-being. A common psychological symptom experienced by patients is a significant decline in self-esteem. Breast cancer patients may experience poor mental health due to their physical condition and the treatment process, making support from those closest to them—especially family—crucial. This study aims to examine the relationship between family support and self-esteem in breast cancer patients undergoing palliative care at Ulin Regional Hospital, Banjarmasin. The study employed a quantitative, correlational research design with a cross-sectional approach. The sampling technique used was consecutive sampling, involving 83 breast cancer patients. Data collection was conducted using a questionnaire. Data analysis utilized Spearman's correlation test. The results showed a relationship between family support and self-esteem among patients, with a correlation coefficient of r = 0.391. The analysis yielded a significance level of p = 0.003, indicating that the alternative hypothesis (H1) was accepted. The correlation coefficient of 0.391 suggests a moderate and positive relationship, meaning that higher family support is associated with higher patient self-esteem. These findings indicate that family support significantly influences and contributes positively to the self-esteem of breast cancer patients.